2018
DOI: 10.1002/syn.22075
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous cannabinoids mediate the effect of BDNF at CA1 inhibitory synapses in the hippocampus

Abstract: Brain‐derived neurotrophic factor (BDNF), traditionally known for promoting neuronal growth and development, is also a modulator of synaptic transmission. In addition to the well‐characterized effects at excitatory synapses, BDNF has been shown to acutely suppress inhibitory neurotransmission; however, the underlying mechanisms are unclear. We have previously shown that at inhibitory synapses in layer 2/3 of the somatosensory cortex, BDNF induces the mobilization of endogenous cannabinoids (eCBs) that act retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…Specifically, alcohol appears to primarily target postsynaptic GABA receptors, whereas cannabinoids seem to target presynaptic CB1 receptors (Kawamura et al, 2006; Sheng and Kim, 2011). Studies done on these receptors in the absence of SAM conditions also support this finding (Chevaleyre and Castillo, 2004; Huang, Lo and Hsu, 2001; Losonczy, Biro and Nusser, 2004; Selvam, Yeh and Levine, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…Specifically, alcohol appears to primarily target postsynaptic GABA receptors, whereas cannabinoids seem to target presynaptic CB1 receptors (Kawamura et al, 2006; Sheng and Kim, 2011). Studies done on these receptors in the absence of SAM conditions also support this finding (Chevaleyre and Castillo, 2004; Huang, Lo and Hsu, 2001; Losonczy, Biro and Nusser, 2004; Selvam, Yeh and Levine, 2019).…”
Section: Discussionmentioning
confidence: 67%
“…In pyramidal cells in layers two/three of the somatosensory cortex, BDNF/TrkB signalling induces postsynaptic eCB release via downstream PLCγ signalling (Yeh, Selvam, & Levine, 2017;Lemtiri-Chlieh & Levine, 2010). Similarly, BDNF/TrkB signalling induces postsynaptic 2-AG release within hippocampal cells (Selvam, Yeh, & Levine, 2019). Both of the aforementioned processes were observed at inhibitory synapses.…”
Section: Bdnf and Ecb Signalling Biosynthesis And Receptor Expressimentioning
confidence: 93%
“…At inhibitory GABAergic neurons in the somatosensory cortex, BDNF signalling induces eCB retrograde suppression of GABA release (Yeh et al, 2017). Likewise, in hippocampal GABAergic neurons, BDNF/TrkB signalling induces 2-AG retrograde suppression of GABA release (Selvam et al, 2019).…”
Section: Synaptic Signallingmentioning
confidence: 99%
“…The authors also showed that treatment restored the baseline excitability and long‐term potentiation (LTP) impaired by stress, showing that the MAGL inhibitor may modify the neuroplasticity in the ventral hippocampal‐nucleus accumbens pathway 32 . Recently, Selvam et al 40 evidenced that in an inhibitory synapse, the activation of the tropomyosin receptor kinase B (TrkB) by BDNF increased the synthesis of 2‐AG. In a retrograde way, 2‐AG acts in CB1 receptors in the presynaptic neuron, suppressing GABA release, consequently reducing the spontaneous inhibitory postsynaptic currents (sIPSCs) in the hippocampus 40 .…”
Section: Mechanisms Of 2‐ag Signalling In Stress and Depressionmentioning
confidence: 99%